2014
DOI: 10.1186/1471-2164-15-s4-s9
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of nucleotide substitutions in the (micro)transcriptome

Abstract: BackgroundRNA-related applications of the next-generation sequencing (NGS) technologies require context-specific interpretations: e.g., sequence mismatches may indicate sites of RNA editing, or uneven read coverage often points to mature form of microRNA. Existing visualization tools traditionally show RNA molecules in two dimensions, with their base pairing and the resulting secondary structure. However, it is not straightforward to combine a linear NGS data display with the 2-D RNA depictions.ResultsWe prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
2
1
Order By: Relevance
“…By analyzing the isomiRs, we observed that A to C substitution was the most abundant occurrence (data not shown), which is not in line with Naqvi et al [78], who found that most of the substitutions comprised A to G and C to T events.…”
Section: Micrornascontrasting
confidence: 79%
“…By analyzing the isomiRs, we observed that A to C substitution was the most abundant occurrence (data not shown), which is not in line with Naqvi et al [78], who found that most of the substitutions comprised A to G and C to T events.…”
Section: Micrornascontrasting
confidence: 79%
“…All detected Drosophila tRFs and their relative read distributions in visual format can be found on our website [ 24 ]; here we illustrate the findings with the two examples of tRFs of different level of abundance, AlaAGC and MetCAT tRFs (Fig. 1 ).…”
Section: Resultsmentioning
confidence: 72%
“…The SIG topics covered in this proceedings issue address: the SNP annotation [ 5 ] from functional [ 6 , 7 ] and structural [ 8 , 9 ] perspectives, the prediction of pharmocogenomic variants [ 10 ] and new drug targets [ 11 ], the visualization of transcriptome genetic variants [ 12 ], and human population models to predict the rate of private variants [ 13 ].…”
Section: Overviewmentioning
confidence: 99%